Teaching Arabic language for foreigners and its trends - Ali, Asem Shehadeh Saleh; Mustapha, Nik Hanan; Chik, Abdul Rahman (s.n, 2012)
The teaching of Arabic as a foreign language is from the fields of Educational linguistics that deals with curriculum, construction, development, and related important issues in the educational process as learner and teacher. This book includes issues related directly to the elements of the educational process, where we find they concerned with teaching Arabic in the four skills, learning from in the level of diverse language, whether in institutions or in universities or in other educational institutions, and finally the issues in education and training which studied between training, methods of education, and computer use in education